(untitled) (Journal of the College of Basic Education, 2022)
The art of comics is one of the arts that has been known since ancient times and has witnessed technical and intellectual developments until it reached what it is at the present time. Despite its importance and its role in enriching art education lessons, this field did not witness the interest of researchers and scholars. In light of this, the current research aims to investigate the role of intellectual and technical developments in comic art in enriching art education lessons. To achieve this, the researcher reviewed previous studies and literature that are related to one or more aspects of the study. The results of the research confirmed the importance of comics art and its impact not only on enriching art education lessons, but its impact was more comprehensive to include children’s personalities and ideas.